BIOMARKERS OF TOBACCO EXPOSURE- RELEVANT DIAGNOSTIC IMPLICATIONS IN DAILY PRACTICE - Ramona Miron; Letitia Trofor; Daniela Bucur; Milena Man; Roberta Cernat; Antigona Trofor (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study was to present available data on biomarkers of tobacco exposure and to inform about their utility in daily practice, focusing on expertise in the field in the Clinic of Pulmonary Diseases of Iasi, Romania. Data overview Smoking status declared by patients must be objectively validated by biochemical tests to determine biomarkers of tobacco exposure. The main biomarkers utilized by practitionners are: carbon monoxide in expired air and plasma, saliva, urine, hair and intranasal cotinine. More recently, researchers have studied also the role of some new biomarkers: anatabine, anabasine, thyocianate, serum uric acid and nitric oxide in expired air. We present up to date data about advantages and disadvantages of each such biomarker and practical details on clinical use, as some of them are also markers of chronic airway inflammation. Conclusions Laboratory tests for tobacco biomarkers offer the opportunity to measure constituents of tobacco smoke and to show exposing to toxicants in tobacco, regardless smoking behavior. In daily clinical practice of the Clinic of Pulmonary Diseases of Iasi have been succesfully introduced carbon monoxide and nitric oxide in exhaled air, serum uric acid and urinary cotinine determinations.